Printed and IT THOTSIC as a Benchmark of Students’ Ability in Facing the National Examination - Sa’adah, Siti Imroatus; Putri, Manju Andika; Nurhasanah, Nurhasanah; Linda, Roza (FKIP-Universitas Riau, 2019)
This research aims to determine the characteristics of THOTSIC in class X chemistry material and to develop a valid and reliable package of questions. The results of PISA study in 2015 showed that the performance of Indonesian students was still relatively low. National Examination, as a benchmark for national standards, should consist of questions component with higher level thinking skills. Chemistry is a central science because it connects various other scientific fields. This is development research based on Research & Development (R & D) using the Plomp model. The results showed the average score of the material expert validator assessment was 99.27%. Limited trials consisted of 1 chemistry teacher and 10 students in class XI. Data analysis showed that teachers’ response questionnaires were 4.93 as a very good category and students’ were78.95% as a good category. The analysis of the reliability level of the questions was 0.62 in the high category level. The level of difficulty of the questions was 0.3 as a difficult criteria and the problem differentiator was 0.39, Dp≥0.3 = as the question was accepted.